2022
DOI: 10.46234/ccdcw2022.030
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening Community Defenses to Prevent and Control the Spread of COVID-19 in China

Abstract: In light of the severity of coronavirus disease (COVID-19) around the world, it is an arduous task for China to prevent COVID-19 from being imported from abroad and proliferating domestically. The community is the first and most effective line of defense and can effectively cut off the channels of spread of the epidemic. In order to reduce risks of COVID-19 transmission in the community, it is necessary to sort out the loopholes in risk and management, as well as investigate previous epidemic transmission even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…The conclusion of the study suggested that restriction measures reduce transmission and unknown contacts that can be difficult to trace, and the response stresses rapid and targeted action to bring new infections under control in regions with large elderly populations and limited healthcare resources, and it has enabled the country to keep infection and fatality rates very low. Also, similar to our findings, the scientists showed similar approach has been successfully adopted to rapidly subdue several waves of COVID-19 caused with Omicron BA.2 in China [35,36]. In addition, a large number of established fact proved that effective measures are not taken to respond to Omicron, and the the epidemic will not stop even if the vaccination rate is high [37][38][39], it can cause massive infections, severe infections and many deaths, especially in a country with a large elderly population and a large number of people with chronic illnesses who are at high risk of severe morbidity and mortality [37][38][39].…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The conclusion of the study suggested that restriction measures reduce transmission and unknown contacts that can be difficult to trace, and the response stresses rapid and targeted action to bring new infections under control in regions with large elderly populations and limited healthcare resources, and it has enabled the country to keep infection and fatality rates very low. Also, similar to our findings, the scientists showed similar approach has been successfully adopted to rapidly subdue several waves of COVID-19 caused with Omicron BA.2 in China [35,36]. In addition, a large number of established fact proved that effective measures are not taken to respond to Omicron, and the the epidemic will not stop even if the vaccination rate is high [37][38][39], it can cause massive infections, severe infections and many deaths, especially in a country with a large elderly population and a large number of people with chronic illnesses who are at high risk of severe morbidity and mortality [37][38][39].…”
Section: Discussionsupporting
confidence: 89%
“…The World Health Organization (WHO) warned that lifting lockdown restrictions may trigger a COVID-19 resurgence, but prolonged lockdown may lead to economic collapse in long term [2,46]. Some studies reported the short-term and long-term effects of COVID-19 control strategies of different intensities on economic development from the perspective of supply chains [5,36]. The losses incurred by the supply chain from strong restrictive measures were largely dependent upon the duration (primary significance) and severity (secondary significance) of the lockdown and other suppression strategies [5,36].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since March 2020, China has been containing successive sporadic clusters of COVID-19 infection through its "dynamic zero-COVID" policy -by mass lockdowns, universal compulsory testing of entire districts or even whole cities, stringent quarantine and isolation enforced down to the neighbourhood level, universal digital contact tracing and importation controls 1,2 . Although this zero-COVID strategy had remained effective in 2020-2021, the emergence and spread of Omicron since early 2022 has triggered prolonged lockdowns and major disruptions in megacities such as Beijing and Shanghai, with ramifications far beyond its own shores nationally and globally in terms of the economy, trade, and commerce.…”
Section: Introductionmentioning
confidence: 99%